Ashis Nandy and the cultural politics of selfhood - Deftereos, Christine (SAGE Publications, 2013)
Ashis Nandy and the Cultural Politics of Selfhood gives the reader an insight into a novel aspect of Nandy. The author insists that Ashis Nandy is not merely a self-described political psychologist; he is also an intellectual street fighter who comes face to face with the psychology of politics and the politics of psychology, thus affirming why this intellectual is one of the most original and confronting Indian thinkers of his generation. The main features of this book are its original reading and the authentic use of the psychoanalytic theory to characterise and demonstr.